2018 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS) 2018
DOI: 10.1109/iros.2018.8594162
|View full text |Cite
|
Sign up to set email alerts
|

New Approach of Cycling Phases Detection to Improve FES-Pedaling in SCI Individuals

Abstract: FES allows spinal cord injured individuals to propel tricycles by means of their own leg power. The stimulation patterns are in most of the cases predefined and muscle activation triggered on the basis of the pedal position. This requires an empirical tuning to fit the pattern to the pilot sitting position and distance to crank with no possible generalization and no adaptive properties. The aim of the present article is to introduce a new approach of motion segmentation based on inertial measurement units loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…If other volunteers had participated in the experiment, the mechanical adjustments would have to be carried out individually, which would have demanded a relative effort to define the best FES pulse parametrization (i.e., the stimulation range of each angle). Studies have suggested the use of IMUs as a better approach for cycling phase detection, which could reduce this effort and improve FE -pedaling by SCI individuals [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…If other volunteers had participated in the experiment, the mechanical adjustments would have to be carried out individually, which would have demanded a relative effort to define the best FES pulse parametrization (i.e., the stimulation range of each angle). Studies have suggested the use of IMUs as a better approach for cycling phase detection, which could reduce this effort and improve FE -pedaling by SCI individuals [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Conventionally, FES onset is determined by the crank position, which is measured by an encoder or an inertial measurement unit. Inertial measurement units can also be placed on the pilot's legs to directly measure the knee angle (38,44) or thigh inclination, indicating the knee flexion or extension phase (45,46), as input in the FES control system. Mechanomyography sensors have been used to monitor muscle activity in real time during stimulation and supervise muscle fatigue (47,48).…”
Section: Devices and Methodsmentioning
confidence: 99%
“…To address this, an approach that does not rely on a predefined geometrical model of the legs is required in order to automatically adapt stimulation timings to dynamic changes (e.g., seating position). In the last years, some research groups have proposed to replace the crank angle encoder with inertial measurement units (IMU) located on the user’s limbs [ 15 , 16 , 17 , 18 ]. Inertial measurement units placed on anatomical segments allow for generic and adaptive ways of defining the stimulation patterns based on leg movement criteria (i.e., maximum knee flexion/extension) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%